ECONOMIC SECURITY OF INNOVATION ORIENTED ENTERPRISES IN TERMS OF EUROPEAN INTEGRATION - Ліна Петрівна Артеменко (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2015)
The article identified the concept of economic security. Determined the role of economic security of enterprises in enhancing the economic security of country in terms of European integration. Determined the concepts of "innovation-oriented enterprise" and "economic security of innovation-oriented enterprises." Considered the structure and assessment of economic security of innovation-oriented enterprises. Determined the basic problems of providing economic security of innovation-oriented enterprises in terms of European integration. Attention is given to the factors of influence of the external environment on economic security of innovation-oriented enterprises of building materials of Ukraine. Discovered weight coefficients of each of groups of factors, also was determined the probability of the negative impact of group factors on economic safety of innovation-oriented enterprise of building materials. The generalized graphical model of the negative impact of the components of economic security of innovation-oriented enterprises of building materials. Determined that one of the ways for the creation of private enterprises prerequisites for economic survival in market conditions is to identify and neutralize threats to the economic stability of the company.